Answer: 4(x + 9) = 3x − 8 − 5
Step-by-step explanation:
Hi, to answer this question we have to analyze the equation given:
4(x + 9) + 5 = 3x − 8
The subtraction property of equality states that if we subtract the same number from both sides of the equation, the equality remains.
So, if we subtract 5 from both sides:
4(x + 9) + 5-5 = 3x − 8 -5
4(x + 9) = 3x − 8 − 5
Feel free to ask for more if needed or if you did not understand something.
Step 1: Set the two equations equal to each other and solve for x.
3x -5 = 6x - 8
3x + (-5+5) = 6x -8 + 5
(3x - 6x) = (6x - 6x) - 3
-3x/-3 = -3/-3
x = 1
Step 2: To solve for y take one of the given equation of your choice (for the purpose of this explanation I will only do y = 3x - 5) and replace x with 1, then solve for y
y = 3(1) - 5
y = 3 - 5
y = -2
(1,-2)
Check:
-2 = 3(1) - 5 ---> - 2 = -2
-2 = 6(1) - 8 ---> -2 = -2
Hope this helped!
1% of $32K is $320
5% of $32K is $1600
$1600 + $320 = 6%
TOTAL IS $1920
I believe y=x+2 and y=-x+3 are perpendicular lines.
A x B x C = 0
Where A and B are integers > 10
Any value multiplied by 0 = 0
Therefore C = 0